Minimax production planning in failure prone manufacturing systems - Boukas, E.K.; Yang, H.; Zhang, Q. (Proceedings of 1995 34th IEEE Conference on Decision and Control, 1995)
Considers a minimax production planning model of a flexible manufacturing system with machines that are subject to random breakdown and repair. The objective is to choose the rate of production that minimizes the related minimax cost of production and inventory/shortage. The value function is shown to be the unique viscosity solution to the associated Hamilton-Jacobi-Isaacs (HJI) equation. Under certain conditions, it is shown that the value function is continuously differentiable. A verification theorem is given to provide a sufficient condition for optimal control. Finally, two examples are solved explicitly.